UNABHÄNGIGKEIT DER JUSTIZ IN DER UKRAINE: AKTUELLER STAND UND MÖGLICHKEITEN ZUR VERBESSERUNG - Moskvych, Lidiia (European Science, 2024)
The article analyses the state of independence of the judiciary in Ukraine. Based on the methodology for assessing the state of independence of the judiciary used in the EU, the author analyses the regulatory guarantees and effectiveness of the mechanism